Compounds originating from the edible mushroom Auricularia auricula-judae inhibit tropomyosin receptor kinase B activity - Orr Shahar; Idan Pereman; Hazem Khamisie; Nirit Ezov; Ofer Danay; Ali Khattib; Ron schweitzer; Soliman Khatib; Jamal Mahajna (Heliyon, 2023)
Tropomyosin receptor kinase B (TrkB) serves as a pivotal factor in various cancers. To identify novel natural compounds with TrkB-inhibiting properties, a screening approach was applied using extracts from a collection of wild and cultivated mushroom fruiting bodies, and Ba/F3 cells that ectopically express TrkB (TPR-TrkB). We selected mushroom extracts that selectively inhibited proliferation of the TPR-TrkB cells. We then evaluated the ability of exogenous interleukin 3 to rescue growth inhibition by the selected TrkB-positive extracts. An ethyl acetate extract of Auricularia auricula-judae actively inhibited auto-phosphorylation of TrkB. LC–MS/MS analysis of this extract revealed substances that might be responsible for the observed activity. This screening approach demonstrates, for the first time, that extracts originating from the mushroom A. auricula-judae exhibit TrkB-inhibition properties that might hold therapeutic potential for TrkB-positive cancers.